2006
DOI: 10.1055/s-2006-944632
|View full text |Cite
|
Sign up to set email alerts
|

A new method of diagnosing gastric intestinal metaplasia: narrow-band imaging with magnifying endoscopy

Abstract: In narrow-band imaging with magnifying endoscopy, observation of a light blue crest on the epithelial surface in the gastric mucosa is a highly accurate sign of the presence of histological intestinal metaplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
300
3
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(327 citation statements)
references
References 10 publications
(10 reference statements)
8
300
3
9
Order By: Relevance
“…Because this study employing Congo-red chromoendoscopy confirms the significance of non-acid-secreting areas as the origin of carcinogenesis after eradication, further trials for the identification of such high risk areas with recently advanced endoscopy, such as high-resolution endoscopy with narrow band imaging (NBI) (Uedo et al 2006;Bansal et al 2008), should be a promising approach for estimating the individual cancer risk in subjects after eradication. Interestingly, a recent study has shown that, in patients with fundic atrophy, the re-emergence of the normal fundic fine structure (fundic pit) after eradication could be detected by magnifying endoscopy (Yagi et al 2005).…”
Section: Discussionsupporting
confidence: 58%
“…Because this study employing Congo-red chromoendoscopy confirms the significance of non-acid-secreting areas as the origin of carcinogenesis after eradication, further trials for the identification of such high risk areas with recently advanced endoscopy, such as high-resolution endoscopy with narrow band imaging (NBI) (Uedo et al 2006;Bansal et al 2008), should be a promising approach for estimating the individual cancer risk in subjects after eradication. Interestingly, a recent study has shown that, in patients with fundic atrophy, the re-emergence of the normal fundic fine structure (fundic pit) after eradication could be detected by magnifying endoscopy (Yagi et al 2005).…”
Section: Discussionsupporting
confidence: 58%
“…This technique provides better details of the mucosa and vascular patterns of minute lesions, including early gastric adenocarcinoma and GIM [9,10] . Uedo et al [11] reported on the excellent accuracy (91%) of the light blue crest (LBC) pattern detected by NBI in predicting the likelihood of GIM. Using a similar method but without magnification, a group from Missouri demonstrated that the ridge/villous pattern of the gastric mucosa detected by NBI was also useful for the diagnosis of GIM, with a sensitivity and specificity of 80% and 100%, respectively [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Bansal et al [13] indicated the microsurface structure of ridge/villous pattern in magnifying NBI images for IM had sensitivity of 80% and specificity of 100%, respectively. We found that a fine light bluish line of light on the epithelial surface or gyri, light blue crest, as a specific finding of IM (sensitivity 89% and specificity 93%) [14]. These types of new endoscopic imaging should enable endoscopists to diagnose certain patients with open-type atrophic gastritis as those with metaplastic gastritis (Fig.…”
mentioning
confidence: 76%